US Refusal to Recognize China (1949–1979) - Gunter, Michael M. (Cappadocia Journal of Area Studies, 2020)
This paper scrutinizes why the United States (US) refused to recognize the People’s Republic of China (PRC) for three decades after its foundation by Mao Zedong in 1949. The traditional national character influenced the position of the US toward the PRC, especially in light of its abhorrence of communism and its doctrine to contain its spread. For both domestic and foreign reasons, the US argued that China was not a responsible member of the world community, and thus deserved no recognition. For more than two decades, the US applied political, economic and diplomatic pressure on the United Nations to refuse the PRC the right to represent China. The situation only began to change when the Nixon administration realized how its non-recognition policy was becoming increasingly outdated and self-defeating, given China’s growing importance in international affairs. This paper will use a variety of primary and secondary sources to analyze the US policy of non-recognition of the PRC, providing the background for a better comprehension of contemporary Sino-American relations.